Controversies and the metaphysics of mind - Senderowicz, Yaron M. (Controversies ;, 2010)
Since ancient times, metaphysical theories have been shaped by the dialectical relations between metaphysical positions. The present book offers a new account of the role of controversies in the evolution of ideas in current metaphysics of mind. Part One develops a pragmatic theory of metaphysical controversies that combines Kantian themes and themes from current argumentation theory. The theory developed in this book underscores the role of a unique type of dialectical arguments which establish metaphysical positions as controversial relevant alternatives in the evolution of chains of debates.